PLAYFULNESS AND MATHEMATICAL LEARNING: GAMES AS EDUCATIONAL TOOLS - Cândido, Vitória Lindaura Eufrásio; Pereira, Tiago Emanoel Melo (Seven Editora, 2026)
This work presents the use of games as a pedagogical resource to make the teaching of Mathematics more dynamic, attractive, and meaningful, as well as to reduce resistance to the subject. The proposal was developed through a project entitled “Mathematical Challenges: Developing Logical Thinking through Games”, implemented in a 9th-grade class. Several activities were applied that promoted problem-solving, spatial visualization, decision-making, and the development of socio-emotional skills. Grounded in the works of authors such as Vygotsky, Grando, Kishimoto, Borasi, and Freire, the study demonstrates that playfulness, recreational mathematics, and mathematical modeling are effective strategies for bringing content closer to students’ realities, fostering a collaborative and enjoyable learning environment. DOI: https://doi.org/10.56238/sevened2026.008-060